Periodic structures : mode-matching approach and applications in electromagnetic engineering - Hwang, Ruey-Bing; IEEE Xplore (Online Service); John Wiley & Sons ([Hoboken, New Jersey] : John Wiley & Sons Inc., 2013)
In Periodic Structures, Hwang gives readers a comprehensive understanding of the underlying physics in meta-materials made of periodic structures, providing a rigorous and firm mathematical framework for analyzing their electromagnetic properties. The book presents scattering and guiding characteristics of periodic structures using the mode-matching approach and their applications in electromagnetic engineering. . Provides an analytic approach to describing the wave propagation phenomena in photonic crystals and related periodic structures. Covers guided and leaky mode propagation in periodic surroundings, from fundamentals to practical device applications . Demonstrates formulation of the periodic system and applications to practical electromagnetic / optical devices, even further to artificial dielectrics. Introduces the evolution of periodic structures and their applications in microwave, millimeter wave and THz.. Written by a high-impact author in electromagnetics and optics. Contains mathematical derivations which can be applied directly to MATLAB programsThe book is primarily intended for graduate students in electronic engineering, optics, physics, and applied physics, or researchers working with periodic structures. Advanced undergraduates in EE, optics, applied physics applied math, and materials science who are interested in the underlying physics of meta-materials, will also be interested in this text.
7.2 Refractive Index of a 2D Periodic Medium 287 -- 7.2.1 Conclusion 291 -- 7.3 An Artificial Dielectric Made of 1D Periodic Dielectric Layers 292 -- 7.3.1 Effective Refractive Index of the 1D Dielectric Periodic Medium 293 -- 7.3.2 Effective Wave-Impedance of the 1D Dielectric Periodic Medium 293 -- 7.4 Conclusion 295 -- References 295 -- Index 297.
In Wiley online library
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web
Description based on PDF viewed 12/22/2015.
Keywords: Electric filters; Optoelectronic devices; Wave guides; Antennas (Electronics); Photonic crystals; Crystal lattices -- Electric properties; Electromagnetic waves; Electronic books